The BecA-ILRI Hub—An African centre for excellence in agricultural biosciences - International Livestock Research Institute (International Livestock Research Institute, 2016)
Agriculture is widely recognized as a key driver of inclusive and sustainable economic growth in Africa. The need to harness biosciences-based innovations to capitalize on agriculture’s potential underpinned the vision of the African Union’s New Partnership for Africa’s Development (AU/NEPAD) initiative leading to the establishment of biosciences “centres for excellence” across the continent. One such centre is the Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub located in Nairobi, Kenya. A co-creation of AU/NEPAD and ILRI, this world class research platform facilitates research by African scientists and their international partners to solve some of Africa’s key agricultural challenges.